Acoustic sorting of microfluidic droplets at kHz rates using optical absorbance. Issue 1 (6th December 2022) - Richter, Esther S.; Link, Andreas; McGrath, John S.; Sparrow, Raymond W.; Gantz, Maximilian; Medcalf, Elliot J.; Hollfelder, Florian; Franke, Thomas
Abstract : We combine acoustic sorting and absorbance detection for ultra-high throughput label free droplet sorting. Abstract : Droplet microfluidics allows one to address the ever-increasing demand to screen large libraries of biological samples. Absorbance spectroscopy complements the golden standard of fluorescence detection by label free target identification and providing more quantifiable data. However, this is limited by speed and sensitivity. In this paper we increase the speed of sorting by including acoustofluidics, achieving sorting rates of target droplets of 1 kHz. We improved the device design for detection of absorbance using fibre-based interrogation of samples with integrated lenses in the microfluidic PDMS device for focusing and collimation of light. This optical improvement reduces the scattering and refraction artefacts, improving the signal quality and sensitivity. The novel design allows us to overcome limitations based on dielectrophoresis sorting, such as droplet size dependency, material and dielectric properties of samples. Our acoustic activated absorbance sorter removes the need for offset dyes or matching oils and sorts about a magnitude faster than current absorbance sorters.